Rapid stimulation of sodium intake combining aldosterone into the 4th ventricle and the blockade of the lateral parabrachial nucleus. (27th March 2017) - Gasparini, S.; Melo, M.R.; Leite, G.F.; Nascimento, P.A.; Andrade-Franzé, G.M.F.; Menani, J.V.; Colombari, E.
Highlights: Central administration of aldosterone induces strong natriorexigenic response. Natriorexigenic response of aldosterone depends on hindbrain mechanisms. Inhibitory mechanisms restrain acute natriorexigenic response of aldosterone. LPBN mechanisms inhibit the natriorexigenic response of aldosterone. Abstract: Chronic infusion of aldosterone into the 4th ventricle (4th V) induces robust daily sodium intake, whereas acute injection of aldosterone into the 4th V produces no sodium intake. The inhibitory mechanism of the lateral parabrachial nucleus (LPBN) restrains sodium intake induced by different natriorexigenic stimuli and might affect the acute response to aldosterone into the 4th V. In the present study, 1.8% NaCl and water intake was tested in rats treated with acute injections of aldosterone into the 4th V combined with the blockade of the inhibitory mechanisms with injections of moxonidine (α2 adrenergic/imidazoline agonist) or methysergide (a serotonergic antagonist) into the LPBN. Male Holtzman rats with stainless steel cannulas implanted in the 4th V and bilaterally in the LPBN were used. Aldosterone (250 or 500 ng) into the 4th V combined with vehicle into the LPBN induced no 1.8% NaClintake compared to control (1.5 ± 1.1 and 1.1 ± 0.4, respectively, vs. vehicle into 4th V: 1.0 ± 0.5 ml/2 h). However, aldosterone (250 or 500 ng) into the 4th V combined with moxonidine (0.5 nmol) into the LPBN induced strong ingestion of 1.8% NaCl (12.7 ± 4.6 and 17.6 ± 3.7 ml/2 h, respectively). Aldosterone (250 ng) into the 4th V combined with methysergide (4 μg) into the LPBN also induced 1.8% NaCl intake (17.6 ± 5.4 ml/2 h). These data suggest that the inhibitory mechanisms of the LPBN counteract the facilitation of sodium intake produced by aldosterone injected into the 4th, restraining sodium intake in this condition.